ANALISIS PENGGUNAAN SIMBOL DAN PENANDA METAFORIS PADA IDENTITAS KARAKTER FILM “FIKSI” KARYA MOULY SURYA - Garcia Iktia (Universitas Negeri makassar, 2025)
The rapid expansion of the Indonesian film industry has led to significant developments, marked by the emergence of diverse themes and genre variations that serve both entertainment purposes and the communication of messages to targeted audiences. This study explores the symbolic meanings presented in “FIKSI”, a film by Mouly Surya that marks an important milestone in the development of the psychological thriller genre in Indonesia. Using a qualitative approach through content analysis and historical examination, the research highlights how the film’s symbolic elements construct a complex narrative layer and create a distinctive psychological experience for its audience. The findings show that the visual and narrative symbols in “FIKSI” not only strengthen the characters and storyline but also pave the way for broader exploration of new genres in Indonesian cinema, positioning the film as a significant reference point in the evolution of national film aesthetics and themes